1998
DOI: 10.1128/jvi.72.5.3789-3795.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cleavage Mutants on Syncytium Formation Directed by the Wild-Type Fusion Protein of Newcastle Disease Virus

Abstract: The effects of Newcastle disease virus (NDV) fusion (F) glycoprotein cleavage mutants on the cleavage and syncytium-forming activity of the wild-type F protein were examined. F protein cleavage mutants were made by altering amino acids in the furin recognition region (amino acids 112 to 116) in the F protein of a virulent strain of NDV. Four mutants were made: Q114P replaced the glutamine residue with proline; K115G replaced lysine with glycine; double mutant K115G, R113G replaced both a lysine and an arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…A similar situation has been reported for NDV, although intracellular cleavage is limited by the presence of a single basic residue at the cleavage site [46,53]. This leads to the F protein being cleaved and fusion triggered only when trypsin and low pH are applied at the cell surface [53,90], as observed in this study ( Fig 4A). This would explain why the same ISAV F proteins coupled with a full length HPR HE did not show any fusion activity when cell monolayers were left untreated ( Fig 4C).…”
Section: Discussionsupporting
confidence: 86%
“…A similar situation has been reported for NDV, although intracellular cleavage is limited by the presence of a single basic residue at the cleavage site [46,53]. This leads to the F protein being cleaved and fusion triggered only when trypsin and low pH are applied at the cell surface [53,90], as observed in this study ( Fig 4A). This would explain why the same ISAV F proteins coupled with a full length HPR HE did not show any fusion activity when cell monolayers were left untreated ( Fig 4C).…”
Section: Discussionsupporting
confidence: 86%
“…Viral genes were inserted into SacI-and XbaI-cut plasmid DNA. Two mutants with mutations of the F gene with altered cleavage sites, mutants F115G and F117L, have been described previously (30,35).…”
Section: Methodsmentioning
confidence: 99%
“…Transfections. Transfections with dioleoyl-L-␣ phosphatidylethanolamine (DOPE) were done essentially as described previously (8,30). Briefly, Cos-7 cells were plated at 2 Ï« 10 5 per 35-mm plate and transfected 18 h later (the monolayers were 50 to 80% confluent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this complex method of proteolytic activation remains unclear, but the cathepsin activation of henipavirus F proteins cannot be functionally replaced by other proteases, as a Nipah F protein mutant containing trypsin-or furin-cleavable sites displays reduced F processing [55]. Cleavage of the Hendra and Nipah F proteins occurs at a monobasic cleavage site GDV-K/R [56,57]; however, mutagenesis studies demonstrated that mutation of the basic residue at the cleavage site or of amino acids upstream of this site did not eliminate F protein processing [57,58], contradictory to other viral fusion proteins [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%